Method of gas-chromatographic measurement of the content of volatile organic substances in the composition of food products - S. A. Romanchikov (Новые технологии)
The article considers the design of the device, the work of which is based on the principles of chromatography to identify the mobile phase of volatile organic compounds in food. The structure of the device allows to analyze the amount of volatile substances released by the test sample, and to compare this amount with similar data for fresh food. A comparative analysis of the results of measuring the content of volatile organic substances with reference values of the quality indicators of food products is carried out automatically. The results of the examination are displayed on the monitor in alphanumeric format. Chromatographic method of investigation allows to determine quantitative values of food quality (freshness) indicators for the content of ammonia, hydrogen sulphide and alcohol vapors in them.